Factors affecting the underwater phase of the swimming start - Tor, E.; Pease, D.; Ball, K.; Farrow, D. (Victorian Institute of Sport, 2015)
Vortrag auf dem Young Experts Workshop - Swim Start Research" 2015 in Kassel mit biomechanischer Betrachtung des Schwimmstarts. Bachground: Start performance is highly related to overall competition performance. •The use of the kick-start has been proven to be advantageous. •The kick-start technique has not widely been researched. •Even less research on the underwater phase of the kick-start technique. Overall aim: •To investigate the factors that affect the underwater phase of the swimming start. Specific aims: •To use a novel multi-disciplinary approach to investigate the swimming start. •To use biomechanical feedback to train swimmers to their ideal underwater trajectory Outline: •Study 1 -Reliability of the WetplateAnalysis System. •Study 2 -Characteristics of an elite swimming start. •Study 3 -Key parameters of elite swimming start performance. •Study 4 -Do swimmers always perform better using their preferred technique? •Study 5 -Comparing three underwater trajectories •Study 6 -How does drag affect the underwater phase of the swimming start? •Study 7 -Can biomechanical feedback be used to change the underwater trajectory of the swimming start? Implications of findings: •Biomechanical feedback can be used as an effective tool to alter start performance. •Individualised approaches to technique improvement using biomechanical feedback should be considered more in the future, particularly with elite athletes. •Sport Scientists and Coaches should be careful not to overload athletes when providing feedback. Practical applications: •There is a lot that can be done during the underwater phase to reduce deceleration. •Biomechanical feedback can be useful for improving technique if used properly. •For the greatest improvements in swimming technique use a multi-disciplinary approach. Take-home messages: •Swimmers will spend the longest amount of time in the underwater phase. •The fastest starters are the ones that can maintain the highest velocity for the longest. •Keep it simple.